Comparison of the Efficacy of Levothyroxine Suppression Dose Computed Based on Actual Body Weight vs. Lean Body Mass among Differentiated Thyroid Cancer Patients: A Randomized Controlled Trial - Lu, Johanna; Rosales, Reynaldo; Dampil, Oliver Allan (Journal of the ASEAN Federation of Endocrine Societies, 2019)
Objective. Comparison of the efficacy of two methods of computation for the initial levothyroxine dose in patients with differentiated thyroid cancer based on actual body weight vs. lean body mass in achieving thyroid-stimulating hormone (TSH) goals. Methodology. Randomized, single-center, 12-week open label controlled trial among adult patients with differentiated thyroid cancer post total thyroidectomy who underwent radioactive therapy at St. Luke’s Medical Center Quezon City from July-December 2018. Participants were divided into 2 groups - Actual Body Weight (ABW) and Lean Body Mass (LBM). Levothyroxine dose was computed based on ABW vs. LBM and TSH determined at 6th and 12th weeks after. Results. Fifty-two participants (ABW n=26; LBM n=26) were included. ABW group had significantly higher mean LT4 dosage (2.2 mcg/kg) compared to the LBM group (1.4 mcg/kg) (p-valuep-value=0.064). A significantly lower TSH level was observed at week 12 in the ABW group (1.6 uIU/mL) compared to the LBM group (3.8 uIU/mL) (p-value=0.010). However, both methods were not associated with achievement of TSH goal at 6th and 12th week (p-value=0.512 and 0.780, respectively). Conclusion. Among patients with differentiated thyroid cancer who underwent 1st time RAI therapy, ABW method of computation for LT4 dosage is better compared to the LBM method due to the lower TSH trend seen at 6th week and statistically significantly lower mean TSH at week 12, although, both method of computations did not achieve target TSH levels at the 6th nor 12th week.